Secure Data Sharing In Cloud by Using CIA (International Journal of Engineering and Computer Science, 2013)
Cloud computing is a type of computing that relies on sharing computing resources rather than having local servers or personal devices to handle applications. The goal of cloud computing is to apply traditional supercomputing, or high-performance computing power, normally used by military and research facilities, to perform tens of trillions of computations per second, in consumeroriented applications such as financial portfolios, to deliver personalized information, to provide data storage or to power large, immersive computer games. To prevent data loss of client an object centered data approach has been proposed. We leverage the JAR programmable capabilities to both create a dynamic and traveling object, and to ensure that any access to users’ data will trigger authentication and automated logging local to the JARs. To strengthen user’s control, we also provide distributed auditing mechanisms. Cloud Information Accountability (CIA) framework, based on the notion of information accountability.